Effect of concentrate supplementation on production performance of ewes grazing on community rangeland - CHATURVEDI, O H; VERMA, D L; SINGH, N P; MANN, J S (The Indian Journal of Animal Sciences, 2011)
Malpura, Kheri and Marwari ewes (40) in their late gestation were randomly selected and divided into 4 groups of 10 each (G1, G2 ,03 and G4). Ewes in G1were maintained on sole grazing while ewes in G2, G3 and 04, in addition to grazing received concentrate pellets at the rate of 1% of their body during late gestation, early lactation and entire last quarter of pregnancy to early quarter of lactation, respectively. The herbage yield of the community rangeland was 2.84-quintal dry matter/hectare. The birth weights of Iambs in 02 and G4 were higher than that in Gland G3. The weight of lambs at 15,30,45 and 60 days of age were higher in G2, G3 and G4 than that in G1. The average daily gain (g) of lambs at 60 days of age was highest in G4, followed by G1, G3 and G2. The nlilk-yield of lactating ewes in G2, 03 and G4 increased up to 150-250 g/day in comparison to G1. The biomass yield 0 the community rangeland is low and insufficient to meet the nutrient requirements of ewes during late gestation and early lactation. Therefore, concentrate supplementation at the rate of 1% of body weight to ewes during these critical stages is recommended to enhance their production performance, general condition as well as birth weight and growth rate of lambs. Â